2005
DOI: 10.1086/497909
|View full text |Cite
|
Sign up to set email alerts
|

Tentative Identification of Interstellar Dust in the Magnetic Wall of the Heliosphere

Abstract: October 8, 2018Two sets of data show that small interstellar grains captured in interstellar magnetic fields, → B IS , draped over the heliosphere appear to polarize the light of nearby stars. The polarizing grains couple to → B IS , while larger grains couple to the cloud velocity. The maximum polarization direction, P max , is offset in ecliptic longitude by ∆λ ∼ +35 o from the upwind direction, and the polarization peak is enhanced for stars near the ecliptic plane. A band of weak polarization stretches thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 68 publications
2
20
1
Order By: Relevance
“…A number of authors have attempted to explain the observed quadrupole-octopole correlations in terms of a new foreground [51][52][53][54][55][56]. (Some of these also attempted to explain the absence of large angle correlations, for which there are also other proffered explanations [57][58][59][60][61][62][63].)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors have attempted to explain the observed quadrupole-octopole correlations in terms of a new foreground [51][52][53][54][55][56]. (Some of these also attempted to explain the absence of large angle correlations, for which there are also other proffered explanations [57][58][59][60][61][62][63].)…”
Section: Discussionmentioning
confidence: 99%
“…(Some of these also attempted to explain the absence of large angle correlations, for which there are also other proffered explanations [57][58][59][60][61][62][63].) Only one of the proposals ( [53]) can possibly explain the ecliptic correlations, as all the others are extragalactic. Some do claim to explain the less-significant dipole correlations.…”
Section: Discussionmentioning
confidence: 99%
“…The S1 subshell parameters used in the above figures correspond to a shell center at (ℓ,b)=(351 • ,−2 • ) and a distance of 78 pc away, a shell radius of 75 pc, and magnetic field angles B θ = 71 • and B φ = −42 • . The dots show stars within 50 pc with polarization data, and the red bars show polarization vectors for stars where polarizations are larger than 2.5σ [66,47,16].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, an obvious possible cause of the anisotropy is contamination by a pernicious foreground (see, e.g., Slosar & Seljak 2004;Bielewicz et al 2005;Copi et al 2006). In this class of explanation, some workers have suggested that the observed quadrupole-octopole alignment might be due to the ReesSciama effect (Rakic et al 2006;Rakic & Schwarz 2007), interstellar dust (Frisch 2005), the presence of local voids (Inoue & Silk 2006), or even the Sunyaev-Zeldovich effect (Peiris & Smith 2010). Another proposal by Vale (2005) argues that the unexpected anisotropy might be due to a moving lens effect associated with the Great Attractor, though its influence may be too small to fully account for the observations (Cooray & Seto 2005).…”
Section: Introductionmentioning
confidence: 99%